Share capital increase strategies and the efficiency of listed companies: A Polish-German comparative analytical study - Artur Sajnóg (Comparative Economic Research. Central and Eastern Europe, 2014)
This paper presents a theoretical-empirical study comprising a comparative analysis of the influence of specific strategies for increasing share capital on the economic efficiency of companies listed on the Polish and German capital markets. The paper consists of three parts. The first part includes the evaluation of possible relations between the efficiency of a company's activities and the process of share capital increase. The second part contains the results of empirical research on changes in share capital in the examined companies, which are listed on the WIG-20 and DAX indices. The third part presents the results of the study on their efficiency in the context of methods applied in order to increase share capital. The assessment of the efficiency of publicly-listed companies was conducted by means of the nonparametric DEA method, using measures oriented on input and constant returns-to-scale. The effects (results) are shown by means of the following ratios: return on sales, return on equity, and return on assets, whereas the inputs are illustrated by ratios of share capital dynamics, financing total assets by share capital and equity dilution.
Keywords: 330; share capital; share capital increase; efficiency; Polish and German joint-stock companies